Inhibition of Hippocampal Aromatization Impairs Spatial Memory Performance in a Male Songbird - Bailey, David J. (Endocrine Society, 2013)
Recent studies have revealed the presence and regulation of aromatase at the vertebrate synapse, and identified a critical role played by presynaptic estradiol synthesis in the electrophysiological response to auditory and other social cues. However, if and how synaptic aromatization affects behavior remains to be directly tested. We have exploited 3 characteristics of the zebra finch hippocampus (HP) to test the role of synaptocrine estradiol provision on spatial memory function. Although the zebra finch HP contains abundant aromatase transcripts and enzyme activity, immunocytochemical studies reveal widespread pre- and postsynaptic, but sparse to undetectable somal, localization of this enzyme. Further, the superficial location of the avian HP makes possible the more exclusive manipulation of its neurochemical characteristics without perturbation of the neuropil and the resultant induction of astroglial aromatase. Last, as in other vertebrates, the HP is critical for spatial memory performance in this species. Here we report that local inhibition of hippocampal aromatization impairs spatial memory performance in an ecologically valid food-finding task. Local aromatase inhibition also resulted in lower levels of estradiol in the HP, but not in adjacent brain areas, and was achieved without the induction of astroglial aromatase. The observed decrement in acquisition and subsequent memory performance as a consequence of lowered aromatization was similar to that achieved by lesioning this locus. Thus, hippocampal aromatization, much of which is achieved at the synapse in this species, is critical for spatial memory performance.